2021
DOI: 10.3390/jof7050384
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Amanitin Biosynthetic Genes and Novel Cyclic Peptides in Amanita molliuscula

Abstract: Amanita molliuscula is a basal species of lethal Amanita and intrigues the field because it does not produce discernable α-amanitin when inspected by High Performance Liquid Chromatography (HPLC), which sets it apart from all known amanitin-producing (lethal) Amanita species. In order to study the underlining genetic basis of the phenotype, we sequenced this species through PacBio and Illumina RNA-Seq platforms. In total, 17 genes of the “MSDIN” family (named after the first five amino acid residues of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Copies of identical MSDIN genes are often linked, which partly causes the patchy patterns. Recent studies showed that most of the MSDIN s are expressed at the transcription level ( 16 , 20 ), and through a genome-guided approach we found 14 cyclic peptides in 5 Amanita species ( 20 , 21 ). Known cyclic peptides are shown in Fig.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Copies of identical MSDIN genes are often linked, which partly causes the patchy patterns. Recent studies showed that most of the MSDIN s are expressed at the transcription level ( 16 , 20 ), and through a genome-guided approach we found 14 cyclic peptides in 5 Amanita species ( 20 , 21 ). Known cyclic peptides are shown in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Whole Genome Shotgun assemblies have been deposited at Data Bank of Japan (DDBJ)/European Nucleotide Archive (ENA)/GenBank under the accession number JAEBUT000000000. We combined these genomes with the genome of G. marginata CBS 339.88, available from the Joint Genome Institute (JGI) MycoCosm database ( 19 ), and the Amanita and Lepiota genomes previously published ( 9 , 11 , 16 , 20 , 21 ). The completeness of the gene repertoires of 13 sequenced genomes, based on Benchmarking Universal Single-Copy Orthologs (BUSCO) and CEGMA (Core Eukaryotic Genes Mapping Approach) analyses, are provided in SI Appendix , Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation